Sibaliparri at Majene Regency West Sulawesi Province (The study of fiqh & the marriage culture of Mandar community) - Sadik, M.; Muhammad, Nuzha; Ridwan, Muh.; Sakinah, Sakinah (Universitas Islam Negeri Ar-Raniry, 2023)
This research examines sibaliparri in terms of fiqh and the culture of Mandar people. It applies qualitative descriptive research which is obtained based on the result of interview of some leaders and Mandar people from various professions and relevant sources. The result of this research states that sibaliparri is one concept of Mandar cultural values which is firmly intimate on society. This image means the concept of togetherness, mutual cooperation also equality in all fields including household life at a time. The implementation of sibaliparri values in household life of Mandar people can be in the picture of understanding, loving each other, mutual cooperation, and sincerity for example when a wife gives a birth then a husband takes over the household matters. Sibaliparri values related to family welfare are reflected in various fields, namely education, home economics, decision making, religious life, and health. Al-Qur’an is a principle and guide about justice which covers various recommendations to enforce economic justice, cultural politic and gender. In general, Al-Qur’an desires women not to be complementary creature and be the second position compared to men. Al-Qur’an provides guide clearly that all humans are equal and not different in terms of gender instead of the level of loyalty and piety. Other hadiths give women more respect than men and argue that women are domestic creatures but their position is fair and proportional, meaning that in certain circumstances men and women have different roles according to their needs and suitability.